2011
DOI: 10.2106/jbjs.j.00315
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Three Weekly Intra-Articular Injections of Hyaluronate on Pain, Function, and Balance in Patients with Unilateral Ankle Arthritis

Abstract: This study suggests that three weekly injections of hyaluronate are well-tolerated and can provide pain relief and improve function and balance in patients with unilateral ankle arthritis. Larger controlled trials with longer follow-up are necessary to verify the effects of hyaluronate in the treatment of ankle arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 27 publications
0
29
0
1
Order By: Relevance
“…All 6 prospective cohort studies evaluating viscosupplementation for osteoarthritis have demonstrated therapeutic efficacy ranging from 6 to 18 months, with the majority of studies including a series of 3 or more injections. [58][59][60][61][62][63] A meta-analysis examining efficacy of viscosupplementation for ankle arthritis concluded that intra-articular hyaluronic acid can significantly reduce pain in ankle osteoarthritis and is likely superior to reference therapy. 64 Viscosupplementation for subtalar joint arthritis has been evaluated in 1 pilot prospective cohort study, which demonstrated analgesic benefit at 28 weeks (AOFAS scores: 54.5 at baseline, 73.7 at week 28; P < 0.01).…”
Section: Therapeutic Rolementioning
confidence: 99%
“…All 6 prospective cohort studies evaluating viscosupplementation for osteoarthritis have demonstrated therapeutic efficacy ranging from 6 to 18 months, with the majority of studies including a series of 3 or more injections. [58][59][60][61][62][63] A meta-analysis examining efficacy of viscosupplementation for ankle arthritis concluded that intra-articular hyaluronic acid can significantly reduce pain in ankle osteoarthritis and is likely superior to reference therapy. 64 Viscosupplementation for subtalar joint arthritis has been evaluated in 1 pilot prospective cohort study, which demonstrated analgesic benefit at 28 weeks (AOFAS scores: 54.5 at baseline, 73.7 at week 28; P < 0.01).…”
Section: Therapeutic Rolementioning
confidence: 99%
“…Karatosun et al (10), in a prospective, randomized-controlled trial of intra-articular HA compared with exercise therapy, did not show any statistically significant differences between the 2 groups at the 12-month follow-up point. Sun et al (11), in their prospective case series of unilateral ankle OA followed up for 6 months, showed significant American Orthopaedic Foot and Ankle Society (AOFAS) scale score improvements using 3 HA intra-articular injections at 1-week intervals. A systematic review found considerable differences among different studies in terms of the number of injections and follow-up length and that this and the paucity of randomized controlled trials meant that a full meta-analysis was not possible (12).…”
Section: Viscosupplementationmentioning
confidence: 99%
“…Currently, in the U.S., HA injections are only FDAapproved for the knee and injections into the ankle, shoulder and hip are considered 'off-label' use 49 . The AOFAS was not able to come to a consensus statement for or against HA injections for ankle arthritis and states that there is an inadequate amount of goof quality research studies examining its efficacy and safety.…”
Section: Viscosupplementationmentioning
confidence: 99%